Modeling information ecology for research community : a case study for system Science Department, FTMSK / Nornafizah Zainudin - Zainudin, Nornafizah (2005)
Information management in research community, not more or less than other businesses or organization, needs to be govem wisely. Since a research community will focus on discovering new finding, the information stored must be able to be share by others, inside or outside the community. Information ecology is a new concept of information management, invented to tackle today's issues. This concept considered both tangible and intangible elements, such as staff and culture that exist in a particular organization or community besides proposing guidance on how to manage the elements from an ecological approach. This paper attempts to suggest new method in managing information in a research community. To accomplish this, both primary and secondary data were used. The paper will first discuss on the potential problem of current management from an ecological point of view. Later section will recommend new approach by adopting information ecology concept.